Millennial Generation's Intention to Use E-Wallet Through the UTAUT2 Model - Emy Widyastuti (Al-Amwal : Jurnal Ekonomi dan Perbankan Syari'ah, 2023)
The quality of implementing new technology is always related to the level of voluntary user acceptance. User acceptance of e-wallet financial technology requires an approach to evaluate the determinants that determine e-wallet acceptance. The Unified Theory of Acceptance and Use of Technology 2 (UTAUT2) model is a synthesis of the appropriate technology acceptance model used for e-wallet evaluation models. This study aims to analyze the influence of Performance Expectancy, Effort Expectancy, Social Influence, Facilitating Conditions, Hedonic Motivation, Price Value, and Habit on Behavior Intention to use the e-wallet. The sample of this research is 100 respondents who come from the millennial generation in the city of Salatiga using a purposive sampling technique. The data analysis technique used is Multiple Linear Regression to determine the relationship of each independent variable to the dependent variable. Based on the research results, it can be concluded that Performance Expectancy and Habit have a positive and significant influence on Behavior Intention. Meanwhile, Effort Expectancy, Social Influence, Facilitating Conditions, Hedonic Motivation, and Price Value has no significant effect on Behavior Intention.